Accounting for multinationals: the Sierra Leone Development Corporation. (2015) - Tinker, Tony
This paper deals with the behaviour of the accounting profession involving multinationals corporations. The Africans were overwhelmed by foreign firms exploiting their labour and raw materials. The minority-elite in power do not intervene to stop such practices. Although Africa is rich in any kind of raw materials, their economic exploitations fail to benefit the populations.